Some solutions to resolve conflicts between parents and teenagers - Hanh, Nguyen Thi Hong (Technium Social Sciences Journal, 2023)
Conflict is inevitable in every relationship, especially in the parent-child relationship. Conflicts can either foster closeness and understanding between the generations or create distance between parents and children. Research has identified six choices of responses when faced with conflicts, categorized based on coping strategies and attitudes towards parents. The specific responses include: 1) Silence; 2) Avoidance; 3) Expressing one’s viewpoint gently to make parents understand; 4) Compliance with parents’ wishes but without happiness; 5) Engaging in intense arguments; 6) Feeling wrong and expressing remorse. Based on this, the study measured two aspects: the satisfaction of adolescents with conflict resolution methods and adolescents’ perception of the impact of conflict resolution on the parent-child relationship using a 4-point scale: 0-Not satisfied at all; 1-Not satisfied; 2-Satisfied; 3-Very satisfied. Additionally, factors influencing conflict resolution were identified, such as the living environment, gender of parents and children.